Synergy between climate and human land-use maintained open vegetation in southwest Madagascar over the last millennium. (February 2022) - Razanatsoa, Estelle; Gillson, Lindsey; Virah-Sawmy, Malika; Woodborne, Stephan
Madagascar experienced environmental change during the Late-Holocene, and the relative importance of climatic and anthropogenic drivers is still the subject of an ongoing debate. Using palaeoecological records from the southwest region at Lake Longiza, we provide additional records to elucidate the complex history of the island and to identify the changes that occurred in the tropical dry forest during the Late-Holocene. The data showed vegetation changes associated with climate variability until AD 900 as reflected by the variation in grass, dry-adapted taxa, deciduous trees, and isotope records. An increasing effect of human activities was recorded, indicated by increased coprophilous spore concentration, as a result of a shift from foraging to pastoralism leading to further opening of the ecosystem from AD 980. At the same time, the regional palaeoclimate record showed drier conditions from around AD 1000, which could have accentuated the changes in vegetation structure. More open vegetation was likely maintained by increased use of fire and herbivory around the area, as indicated by the multiple peaks in the charcoal and spore records. Since AD 1900, the pollen record from the southwest region showed that the ecosystem became increasingly open with an increased abundance of grass, pioneer taxa, and reduced diversity, which was linked to a simultaneous effect of climate and agropastoralism activities. Our study suggests that the dry conditions around AD 950 initiated the replacement of forest-dominant vegetation with grass-dominant communities over the last millennium, depicted as an open ecosystem at present. Subsequent changes in subsistence activities would have further maintained an open-structured ecosystem.